2018
DOI: 10.14687/jhs.v15i2.4895
|View full text |Cite
|
Sign up to set email alerts
|

Determination of healthy lifestyle behaviors of high school students<p>Lise öğrencilerinin sağlıklı yaşam biçimi davranışlarının belirlenmesi

Abstract: This research was conducted as a descriptive study to determine the healthy lifestyle behaviors of high school students. The schools located in Rize Province were grouped (n: 9926). The number of samples was determined to be 370 according to the sample width formula, which is known as the number of individuals in the phase. A total of 449 volunteer students were selected from a high school in each group by simple random sampling method and the study was completed. To collect data, the personal information form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 4 publications
0
5
0
1
Order By: Relevance
“…Coskun and Ozer (2018) stated in their research that physical activity scores for girls at secondary school level are lower than for boys (49). Karaaslan and Celebioglu (2018) found that the physical activity average score of male students is higher than the average score of female students (50). Keskin et al (2017) found that male students' scores were higher than female students in their research with secondary school students (51).…”
Section: Discussionmentioning
confidence: 93%
“…Coskun and Ozer (2018) stated in their research that physical activity scores for girls at secondary school level are lower than for boys (49). Karaaslan and Celebioglu (2018) found that the physical activity average score of male students is higher than the average score of female students (50). Keskin et al (2017) found that male students' scores were higher than female students in their research with secondary school students (51).…”
Section: Discussionmentioning
confidence: 93%
“…Adolescence is a period when physical and mental changes are experienced intensely. Healthy lifestyle behaviors are mostly acquired during adolescence, and those positive or negative behaviors affect individuals throughout their lives [20,21]. Paying attention to cleanliness, healthy lifestyle, and hygiene is remarkable for protecting and maintaining health and preventing health problems [13].…”
Section: Discussionmentioning
confidence: 99%
“…The adherence to hygiene behaviors is known to be affected by a number of factors such as gender, socioeconomic status, and education level [26]. In a study carried out by Karaaslan et al (2018), female high school students were found to have higher health responsibility as compared to male students [21].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, many of the studies (Arslan & Ceviz, 2007;Yalçınkaya, Özer & Karamanoğlu, 2007;Tokuç & Berberoğlu, 2007;Ertop, Yılmaz & Erdem, 2012;Kostak, Kurt, Süt, Akarsu & Ergül, 2014;Ararat & Karagün, 2016;Tedik & Hacıalioğlu, 2017;Mete, Nacar, Tekin & Pehlivan, 2017;Koçak, Öncel, Zincir & Seviğ, 2017;Özkan, 2018;Toktaş, Erman & Yetik, 2018;Karaaslan & Çelebioğlu, 2018;Ardıç & Taşkın, 2018) which used the Healthy Life Style Behavior Scale II (HLSBS-II) are descriptive. Together with the statistical data obtained from these studies, positive contribution was made to the literature on behalf of sub-scales of the HLSBS-II.…”
Section: Discussionmentioning
confidence: 99%